Government Policy on Zakat and Tax in Indonesia - Sudirman Sudirman (Universitas Islam Negeri Jakarta, 2015)
New Order Government tends to consider as zakat and tax liabilities are different. There is an exciting development in the era of reform with the passage of Act No. 38 of 1999 on the Management of Zakat and converted into Act 23 of 2011. It seems that the government has to have the desire to accommodate the charity as potential aspects to reduce taxes. Moreover, the idea of integrating the zakat and taxes in one more incentive system sounded. If this is true, the government may implement two points of maqâshid al-syarî’ah, namely hifzh al-dîn and hifzh al-mâl. DOI: 10.15408/ajis.v15i1.2841